2020
DOI: 10.2147/cmar.s269215
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognostic Significance of Pregnancy Zone Protein and Its Correlation with Immune Infiltrates in Hepatocellular Carcinoma</p>

Abstract: Human pregnancy zone protein (PZP) is a pregnancy-related protein which is increased dramatically during pregnancy. However, the expression of PZP and its prognostic value, association with tumor-infiltrating immune cells (TIICs) in microenvironment and potential biological process in HCC were unclear. Methods: The PZP expression, clinicopathology analysis and its influence on survival were analyzed by GEPIA and HPA. Fifty-nine HCC samples and 30 corresponding noncancerous tissues were collected and retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Previous research has also uncovered the role of PZP in cancers. In hepatocellular carcinoma, PZP has low expression in tumor tissues, and the downregulation of PZP is correlated with poor clinical outcomes [ 35 ]. Our research identified and validated PZP as a novel serum biomarker for screening LAC in patients with T2DM by SWATH-MS, PRM-MS and ELISA analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also uncovered the role of PZP in cancers. In hepatocellular carcinoma, PZP has low expression in tumor tissues, and the downregulation of PZP is correlated with poor clinical outcomes [ 35 ]. Our research identified and validated PZP as a novel serum biomarker for screening LAC in patients with T2DM by SWATH-MS, PRM-MS and ELISA analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, LCAT was hypermethylated and decreased in HCC tissues (40), could act as a good biomarker at predicting HCC diagnosis, prognosis and recurrence (41), and it was confirmed in the later study by Long (42). As for PZP, in previous study we have confirmed that its depletion was significantly related to poor survival outcomes in HCC (16). All these indicated that AURKA, PZP, RACGAP1, ACOT12 and LCAT played important roles in the development of HCC and might be targets for immunotherapeutic intervention strategies in further.…”
Section: Discussionmentioning
confidence: 54%
“…Previous collected 59 fresh frozen tissues from HCC patients were selected as an independent validation cohort (16). qRT-PCR was used to detect the mRNA levels of the five gene (17), after the relative mRNAs expression levels were normalized to b-ACTIN and log 2 transformed.…”
Section: Clinical Specimens and Quantitative Real-time Pcr (Qrt-pcr) Analysismentioning
confidence: 99%
“…In addition, increased PZP concentration in the sputum is associated with respiratory tract infection caused by Pseudomonas aeruginosa [ 23 ]. In hepatocellular carcinoma, the expression of PZP was low in tumor tissue, and the down-regulation of PZP is associated with a poor clinical prognosis [ 36 ]. Recent studies found that PZP mRNA was downregulated in lung cancer tissues and was significantly correlated with immune cell infiltration.…”
Section: Discussionmentioning
confidence: 99%